CRIMINOLOGICAL PERSPECTIVES ON PUBLIC HEALTH DETERMINANTS OF CRIME: A SCOPING REVIEW - Fuad Rizki Gazali,; Viola Widyanita Mahardhika, (Journal of Innovation Research and Knowledge, 2025)
Background: Crime represents a multifaceted social phenomenon that extends beyond legal violations and into the realm of public health. Research increasingly reveals how health-related factors such as mental illness, substance use, trauma, and environmental disadvantage serve as root contributors to criminal behavior. Recognizing crime as a public health issue enables a broader, more integrative approach to prevention and justice reform. Methods: This scoping review aims to map and synthesize empirical and theoretical literature exploring the intersection between criminology and public health. Specifically, it identifies public health determinants associated with criminal behavior and evaluates how criminological frameworks engage with these factors. Results: Following PRISMA-ScR guidelines, we systematically searched PubMed, Scopus, and Google Scholar for English-language articles published between 2013 and 2024. Keywords included "crime," "public health," "mental illness," "substance abuse," "violence," and "social determinants." Eligible studies were charted and synthesized thematically. Conclusion: Criminological inquiry increasingly intersects with public health. Understanding the social and health-related precursors to crime allows for more effective, equitable, and interdisciplinary interventions. Policymakers, law enforcement, and health practitioners must collaborate to address these shared determinants and reduce systemic harm